Perlindungan Hukum terhadap Eksploitasi Anak Melalui Platform Digital Tiktok - Fitria Sari, Cucun Cundaya; Pratama, Yuda (Jurnal Risalah Hukum, 2024)
Sharenting or uploading videos of children's daily lives and/or activities to the TikTok platform can have a negative impact on children. Two of the negative impacts that arise are psychological disorders in children and the potential for criminal acts experienced by the child themselves. This study aims to determine how legal protection is provided for child exploitation by parents through the TikTok platform. The results of the analysis show that sharenting by parents, especially content creators, can lead to child exploitation. Not only that, sharenting can also eliminate children's privacy rights, eliminate other rights that are fundamental rights of children and have a negative effect on children. The Child Protection Act and the Human Rights Act have given obligations and responsibilities to parents and the government and/or the central government to provide legal protection to children and to fulfill the rights of every child. Recommendations that can be given through this study should be that the government can intensify socialization to every parent regarding the importance of knowing and understanding what children's rights are, this is considering that sharenting occurs due to parents' ignorance of children's rights as regulated in the Child Protection Act.